DEVELOPMENT OF ETHNO-CRT LEARNING MODEL TO IMPROVE CRITICAL THINKING SKILLS AND SCIENCE LITERACY IN ECOLOGY AND BIODIVERSITY MATERIALS - Desandra Putri, Enjelina; Sudarmin, Sudarmin; Tri Prasetya, Agung (International Journal of Active Learning, 2025)
This research aims to develop an Ethno-CRT (Culturally Responsive Teaching) learning model based on Ethnoscience to improve students' critical thinking skills and science literacy on ecology and biodiversity materials. This research is a development research using a 4-D model (Define, Design, Develop, and Disseminate). The products developed include Ethno-CRT learning model books, syllabus, lesson plans, science e-modules, as well as critical thinking and science literacy test instruments. The results of validity by experts and readability by students show that the entire Ethno-CRT mitigation model is in the "valid" category and is very worthy of testing. The trial was carried out in two classes, namely class VIIA as an experimental class using the Ethno-CRT model and class VIIB as a control class with the CRTT model. The results of data analysis showed an increase in critical thinking skills and higher science literacy in the experimental class. The n-gain value of critical thinking ability in the experimental class reached 0.71 (high category), while the control class was 0.50 (medium category). For science literacy, the experimental class obtained an n-gain of 0.64 and a control class of 0.40, both in the medium category. So, the Ethno-CRT learning model in science learning ecology and biodiversity materials is very feasible and effective to be used to improve the critical thinking skills and science literacy of junior high school students